2021
DOI: 10.1206/0003-0090.453.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Relictual Asian Scorpion Family Pseudochactidae Gromov, 1998, with a Review of Cavernicolous, Troglobitic, and Troglomorphic Scorpions

Abstract: CONTENTS SIAC gih.Sh o: Petar scat NG gael Marit ts aad oe tle s.r aeet sca de Shale antl Maid te gud ce Vath teal 3 1ACURMOT NU VGLa1S) eR org OR i eT ARRON cede lee arene ated ee hut RE a da ed eee MAME dee 3 Review of Cavernicolous, Troglobitic, and Troglomorphic Scorpions .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…The biospeological classification of Troglorhopalurus lacrau ( Lourenco and Pinto-da-Rocha 1997 ) remains contentious due to it having cave populations in the state of Bahia and one epigean record (of its junior synonym Rhopalurus brejo Lourenço, 2014) from Crato in the state of Ceará ( Esposito et al 2017 ). Based on those records, Esposito et al (2017) classified Troglorhopalurus lacrau as a troglophile, a classification also followed by Prendini et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The biospeological classification of Troglorhopalurus lacrau ( Lourenco and Pinto-da-Rocha 1997 ) remains contentious due to it having cave populations in the state of Bahia and one epigean record (of its junior synonym Rhopalurus brejo Lourenço, 2014) from Crato in the state of Ceará ( Esposito et al 2017 ). Based on those records, Esposito et al (2017) classified Troglorhopalurus lacrau as a troglophile, a classification also followed by Prendini et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Buthidae, the largest scorpion family (~1263 species) (Rein 2021), has few records from subterranean habitats (Volschenk and Prendini 2008;Gallão and Bichuette 2016;Prendini et al 2021), whereas the buthid genus Tityus, the most diverse scorpion genus, has only nine species recorded from caves: Tityus (Tityus) blaseri Mello-Leitão 1931 (Brazil) [probably troglophile]; Tityus (Tityus) confluens bodoquena Lourenço, Cabral & Ramos, 2004 (Brazil) -Sponga 1974;Lourenço 1981;Trajano 1987;Trajano and Moreira 1991;Pinto-da-Rocha 1995;Lourenço et al 1997Lourenço et al , 2004Volschenk and Prendini 2008;Lourenço and Duhem 2010;Botero-Trujillo and Flórez 2014). Recently, Prendini et al (2021) classified T. grottoedensis as trogloxene, and T. demangei, T. magnimanus and T. monaguensis as accidental. However, there are scarce field observations on the dependence on and use of subterranean habitats by most Tityus species.…”
Section: Cave Scorpionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alberti (1983) suggested that the loosely aggregated spermatozoa of the buthid, Buthus occitanus (Amoreux, 1789), represent sperm bundles. The presence of sperm packages also remains unknown in Pseudochactidae Gromov, 1998, considered closely related to Chaerilidae, in superfamily Chaeriloidea Pocock, 1893 (Prendini et al, 2006(Prendini et al, , 2021. Data on sperm packages are also lacking for another 12 families, notably the basal nonbuthid family Iuridae Thorell, 1876, of superfamily Iuroidea Thorell, 1876; five chactoid families, Caraboctonidae , Scorpiopidae Kraepelin, 1905, Superstitioniidae Stahnke, 1940, Troglotayosicidae Lourencgo, 1998, and Typhlochactidae Mitchell, 1971; and six scorpionoid families, Diplocentridae Karsch, 1880, Hemiscorpiidae Pocock, 1893, Heteroscorpionidae Kraepelin, 1905, Hormuridae Laurie, 1896, Rugodentidae Bastawade et al, 2005, and Urodacidae Kraepelin, 1905 The precise function of sperm packages in scorpions is unclear.…”
Section: Introductionmentioning
confidence: 99%